Mobilizing diversity: establishment of the first two community seedbanks in South Africa’s smallholder farming areas - Vernooy, Ronnie; Sthapit, B.R.; Tjikana, Thabo T.; Dibiloane, A.; Maluleke, Nkat Lettie; Moila, P.; Phora, G. (Bioversity International, 2016)
This report presents the findings of the 2015 field missions to Limpopo and Eastern Cape provinces of the Republic of South Africa. The missions aimed to build the technical and organizational capacity of the farmers to be able to manage the community seedbanks independently, with minimum support from Bioversity International and the NPGRC. Physical buildings were built or prepared and farmers in the two project sites contributed seeds for the very first collections of their community seedbanks. Contributing farmers have agreed on the functions and governance and management structures of the community seedbanks, and have learned about seed registration, and seed selection, treatment, storage and maintenance.